Dr. Bruno Hartman in njegov prispevek k razvoju slovenskega knjižničarstva - Sapač, Irena (Knjižnica, 2012)
The article describes Dr. Bruno Hartmans contribution to the development of Slovenian librarianship and his impact on the profession. He researched library history, organization and building and published many articles. he was interested in library legislation and information technology. First he devoted his work to the organization of study, public, school and special libraries, and later to university libraries, too. He was the initiator of the merging of public libraries in Maribor, the establishment of the Association of the Slovenian study libraries, the integration of the Study library into the University of Maribor and its renaming into the University of Maribor library. He realized his vision of the new library building and of the introduction of information technology. He designed study programmes at the Department of librarianship and information studies in Ljubljanaand lectured the students of librarianship. He cooperated actively in the Slovenian library association and in foreign professional associations. He was an editor of the journal Knjižnica.
Keywords: Harman, Bruno, 1924-2011; biografije; library science; bibliotekarstvo; bibliotekarji